2009
DOI: 10.1152/jn.91190.2008
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Activation of GABAB Receptors Reduces Release Probability at Inhibitory Connections in the Cerebellar Glomerulus

Abstract: In the cerebellum, granule cells are inhibited by Golgi cells through GABAergic synapses generating complex responses involving both phasic neurotransmitter release and the establishment of ambient γ-aminobutyric acid (GABA) levels. Although at this synapse the mechanisms of postsynaptic integration have been clarified to a considerable extent, the mechanisms of neurotransmitter release remained largely unknown. Here we have investigated the quantal properties of release during repetitive neurotransmission, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
133
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(148 citation statements)
references
References 69 publications
13
133
2
Order By: Relevance
“…While st-LTP was induced when EPSP led AP, st-LTD was induced when AP led EPSP according to the Hebbian principle of coincidence detection between presynaptic and postsynaptic activity. In this respect, mossy fiber-granule cell STDP is similar to that observed at different synapses mostly located in the neocortex and hippocampus (Magee and Johnston, 1997;Markram et al, 1997;Bi and Poo, 1998 first evidence that Hebbian STDP occurs in the cerebellum because previous observations only reported either non-Hebbian STDP at the parallel fiber-Purkinje-like cell synapse (Safo and Regehr, 2008;Piochon et al, 2012) or anti-Hebbian STDP at the corresponding synapses of cerebellum-like structures (Bell et al, 1997;Tzounopoulos et al, 2004;Wu et al, 2015). It should be noted that, different from Purkinje cells, granule cells show a rapid and complete spike back-propagation into the dendrites (Diwakar et al, 2009;Dover et al, 2016), so that information about AP generation can be faithfully transmitted to synaptic sites providing a key requirement for Hebbian STDP.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…While st-LTP was induced when EPSP led AP, st-LTD was induced when AP led EPSP according to the Hebbian principle of coincidence detection between presynaptic and postsynaptic activity. In this respect, mossy fiber-granule cell STDP is similar to that observed at different synapses mostly located in the neocortex and hippocampus (Magee and Johnston, 1997;Markram et al, 1997;Bi and Poo, 1998 first evidence that Hebbian STDP occurs in the cerebellum because previous observations only reported either non-Hebbian STDP at the parallel fiber-Purkinje-like cell synapse (Safo and Regehr, 2008;Piochon et al, 2012) or anti-Hebbian STDP at the corresponding synapses of cerebellum-like structures (Bell et al, 1997;Tzounopoulos et al, 2004;Wu et al, 2015). It should be noted that, different from Purkinje cells, granule cells show a rapid and complete spike back-propagation into the dendrites (Diwakar et al, 2009;Dover et al, 2016), so that information about AP generation can be faithfully transmitted to synaptic sites providing a key requirement for Hebbian STDP.…”
Section: Discussionsupporting
confidence: 66%
“…The error introduced in amplitude measurement by the failures, which have non-0 amplitude due to the indirect response, was eliminated by setting the amplitude of the indirect responses to 0 . To investigate the expression mechanism of STDP D'Errico et al, 2009;Mapelli et al, 2009), a simplified version of quantal analysis was performed by measuring the mean and SD of EPSC amplitude. All measurements were performed over N ϭ 100 contiguous EPSCs minimizing errors introduced by small samples (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute rat cerebellar slices were obtained as reported previously (D'Angelo et al, 1995;Armano et al, 2000;Mapelli et al, 2009). Briefly, 17-to 23-d-old Wistar rats of both sexes were anesthetized with halothane (Sigma-Aldrich) and killed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that, in the lateral superior olive (LSO), GABA B R activation by retrogradely released GABA regulates the balance of excitation and inhibition and thereby adjusts the sensitivity of these neurons to interaural intensity differences (Magnusson et al, 2008). Furthermore, presynaptic GABA B Rs have been implicated in decreasing short-term synaptic depression and might thereby improve faithful synaptic transmission for the represen-tation of sound structure (Brenowitz et al, 1998;Mapelli et al, 2009). Preliminary immunostainings have revealed that in the auditory brainstem GABA B Rs are not only present before hearing onset, when the MNTB releases both GABA and glycine, but also in adult animals, when the MNTB input has become glycinergic (Heise et al, 2005;Hilbig et al, 2007).…”
Section: Introductionmentioning
confidence: 99%